Political Loyalty in Contemporary Islamic Ethics: Sunni and Shii Perspectives - Belhaj, Abdessamad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
This study aims to provide a thorough examination and analysis of the political loyalty discourses of two prominent figures in Sunnism and Twelver Shiism: the Egyptian-Qatari Sunni scholar Yūsuf al-Qaraḍāwī (1926-2022) and the Iraqi Twelver Shii scholar Muḥammad Mahdī al-Āṣifī (1939-2015). I discuss the origins and effects of these perspectives on political allegiance, demonstrating how Sunnism grounds political allegiance in pragmatic ethics and the context of conflict and peace while encouraging equity when interacting with non-Muslims. The Twelver Shii school of thought supports principlist ethics, promoting the idea that political loyalty to people who represent legitimate religious and political authority is an expression of obedience that must be shown without exception. In terms of methodology, I use a discourse analysis method to determine the major thesis of a statement as well as the arguments presented in support of a particular thesis. I place the arguments in the context of the ongoing discussions in Islamic political ethics. Al-Qaraḍāwī and al-Āṣifī agree on the importance of treating non-aggressive Muslims fairly and remaining devoted to the Muslim community. I conclude that there is more space for a flexible ethics of political allegiance and less exclusion between the two schools of thought.